2020
DOI: 10.31729/jnma.5745
|View full text |Cite
|
Sign up to set email alerts
|

Study on Clinico-Demographic Characteristics of Orthopaedic Cases in a Tertiary Care Centre: A Descriptive Cross-sectional Study

Abstract: Introduction: Orthopedic conditions include a range of condition varying from traumatic injuries, congenital anomalies, chronic back-pain, arthritis, rheumatologic conditions, and other. In Nepal, approximately 2.35 million people are living with musculoskeletal conditions in which 175,000 people are suffering with MSD from non-traumatic causes. The aim of the study is to observe the clinical and demographic pattern of orthopedic problems presenting in the hospital. Methods: A descriptive cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
4
2
Order By: Relevance
“…Men (76.45%) were more likely to suffer fractures in this study than women (23.55%), similar to the findings in other Nepalese studies. 5 , 8 Our study found a 3.25:1 male-to-female ratio, while others found it varying from 1.82:1 to 1.52:1. 5 , 8 As per a study from Nepal, the ratio of males to females in India (6:1) and Singapore (2.25:1) differed.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Men (76.45%) were more likely to suffer fractures in this study than women (23.55%), similar to the findings in other Nepalese studies. 5 , 8 Our study found a 3.25:1 male-to-female ratio, while others found it varying from 1.82:1 to 1.52:1. 5 , 8 As per a study from Nepal, the ratio of males to females in India (6:1) and Singapore (2.25:1) differed.…”
Section: Discussioncontrasting
confidence: 52%
“… 5 , 8 Our study found a 3.25:1 male-to-female ratio, while others found it varying from 1.82:1 to 1.52:1. 5 , 8 As per a study from Nepal, the ratio of males to females in India (6:1) and Singapore (2.25:1) differed. 9 , 10 A possible cause could be gender biases in work and educational opportunities and drunk-driving behaviours, particularly in developing countries, such as Nepal, which is dominated by men.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…A similar study conducted by Rijal et al in a tertiary care centre of Nepal reports that 12.44% of implant removal procedures were carried out of the total orthopedic cases admitted to the hospital. 1 Other studies also report a similar type of trend; 13.7% out of patients having prior open reduction and internal fixation operation in a study at a hospital of Ghana by Kuubiere CB et al 3 and 14.1% out of total major and intermediate orthopedic operations carried out three hospitals of Nigeria by Onche I, et al 5 Another study reports 7.83% 2 of implant removal procedures out of total orthopedic and trauma surgery, conducted at a tertiary care center in Nepal, which is relatively low than previously discussed studies. But, in resource-limited places like Nepal, implant removal surgery tends to occupy much of the workforce in day-to-day practice.…”
Section: Discussionmentioning
confidence: 99%
“…Orthopedic implant removal procedures are among the most carried out procedures in the department of orthopedics. 1 …”
Section: Introductionmentioning
confidence: 99%